Not so fast, I am serofast: Using actionable patient education to drive appropriate management of people with serofast syphilis serologies - Dennis Kan; Molly Stenzel; Julie Thompson; Jennie De Gagne; Kara McGee (Journal of the American Association of Nurse Practitioners, 2026)
ABSTRACT Background: An increase in syphilis cases in the United States and the global shortage of Benzathine Penicillin G (BPG) calls for evidence-based optimization. Confusing serologies and incomplete sexual history exacerbate the overprescription of BPG, especially for patients with “serofast” serologies. Purpose: The aim of this project was to reduce unindicated BPG administration while maintaining or improving appropriate BPG administration in people diagnosed with syphilis. Methodology: A longitudinal pre-post design was implemented where actionable education was delivered to patients who received BPG injection to treat syphilis. Results: Benzathine Penicillin G was administered 187 times (69 preintervention, 118 postintervention), and inappropriate administration declined by 7.9% relatively (10.1–9.3%). There was no difference in outcomes between the newly infected and reinfected patients. Conclusion: This project demonstrated modest improvements in the administration of appropriate BPG, although the results did not reach statistical significance. Implications: Future interventions should focus on automating patient education within the electronic health record. The growing prevalence of syphilis among non-traditional risk groups emphasizes the importance of sexual health screening and educational approaches to enable patients to advocate for appropriate syphilis management, especially when they are serofast.